Evaluating the avoidance factors in counselling using fuzzy analytical hierarchy process (AHP) / Nurul Hafizah Alias - Alias, Nurul Hafizah (2020)
Counselling is defined as the establishment of professional assistance and guidance in resolving personal or psychological problems. It involves two communication between counselor and client. The objective of this study is to to analyze the factors that caused students avoid from joining some counselling session. This research is also to rank the main factors of avoidance from joining counselling by using method of Fuzzy Analytic Hierarchy Process (FAHP). The result that obtained from this study indicates that negative stigmation is the first factor of why students do not interest in joining counselling. It followed by treatment fears as the second factor and then the factors of anticipated risk and utility as the third factor of this issues. The significant of this project is to change the negative perception of the students in UiTM Perlis about the counselling. Lastly, this study will open the mind of many people about the importance and the benefits of counselling in order to help to create a better performance of life.